PERSEPSI DIGITALISASI SISTEM ADMINISTRASI CORETAX OLEH KONSULTAN PAJAK DALAM MENINGKATKAN PENERIMAAN PAJAK DI INDONESIA - Riani Tanjung; Desta Alya Putri; Christine Riani Elisabeth (Universitas Merdeka Madiun, 2025)
This study explores the perceptions of tax consultants regarding the Coretax Administration System, a new taxation system introduced by the Directorate General of Taxes in late 2024 to facilitate tax compliance and improve state revenue. Using a qualitative approach and primary data collected through structured interview questionnaires, the findings indicate that the system significantly assists tax consultants in performing their duties. However, unstable server performance remains a notable challenge. Overall, the system is perceived to have substantial potential to support the enhancement of national tax revenue.